Physical ultrasonics of composites. - Stanislav Rokhlin; Dale Chimenti; Peter Nagy (Oxford University Press, 2011)
The objective of this book is to treat the behavior of ultrasonic waves as they interact with layered, anisotropic materials incorporating those structural aspects unique to composite laminates addressing both experimental and modeling methodologies. Anisotropic material interfaces, guided waves, waves in layered media and laminated plates are treated. The influence of finite-aperture transducers on electronic signals and the field of air-coupled ultrasonics end the work.